2005
DOI: 10.1093/aob/mci086
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Atriplex halimus Populations in the Mediterranean Basin

Abstract: The present work indicates that two genetic groups of A. halimus can be distinguished after analysing the genetic diversity of 51 populations from ten countries in the Mediterranean Basin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 10 publications
2
43
0
6
Order By: Relevance
“…Our results are compatible with the pattern of species that are primarily outcrossing and long lived-wind pollinated shrub, which retain most of their genetic variability within populations [43]- [45]. The level of population differentiation 25.81% obtained in this study was lower than that found among 51 A. halimus populations (29.18%) from ten countries in the Mediterranean basin and 12 populations (33.43%) from Morocco, analysed by RAPDs [20]- [41]. However, Ortíz-Dorda et al [20] studied six populations from Egypt (Matrouh area) and they concluded that these populations had the lowest value of genetic diversity among the populations studied and they all were clustered in one group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results are compatible with the pattern of species that are primarily outcrossing and long lived-wind pollinated shrub, which retain most of their genetic variability within populations [43]- [45]. The level of population differentiation 25.81% obtained in this study was lower than that found among 51 A. halimus populations (29.18%) from ten countries in the Mediterranean basin and 12 populations (33.43%) from Morocco, analysed by RAPDs [20]- [41]. However, Ortíz-Dorda et al [20] studied six populations from Egypt (Matrouh area) and they concluded that these populations had the lowest value of genetic diversity among the populations studied and they all were clustered in one group.…”
Section: Discussionsupporting
confidence: 87%
“…However, these subspecies described by Le Houérou are not accepted taxonomical units. Ortíz-Dorda [20] distinguished two genetic groups are rather coincident with the characters described by Le Houérou [1]- [11]. The connection between the two genetic groups described by Ortíz-Dorda [20] and the two subspecies described by Le Houérou [1] is uncertain particularly in our study which revealed the uncertain genetic separation between the two types of morphologies of A. halimus using Start Codon Targeted (SCoT) marker and the sequencing of ITS1-5.8S-ITS2 regions.…”
Section: Discussionmentioning
confidence: 43%
“…Species of the saltbushes Atriplex have been used both as forage and to rehabilitate degraded areas (dunes, salt-mines, saline soils). They are dominant in many arid and semi-arid regions of the world, particularly in environments combining relatively high soil salinity with aridity (Ortiz-Dorda et al, 2005). Quantifying the recovery of the biological activity of soils remediated with plants has been the focus of few studies.…”
Section: Plant Remediation Strategiesmentioning
confidence: 99%
“…Atriplex halimus L., originated from North Africa, is a widespread Mediterranean shrub species (Ortíz-Dorda et al 2005) with high resistance to various abiotic stresses included heavy metals (HM) (Lutts et al 2004;Lefèvre et al 2009). However, since this species shows a high genetic variability (Ortíz-Dorda et al 2005), phytoextraction capacities may greatly vary from one population to another.…”
Section: Introductionmentioning
confidence: 99%
“…However, since this species shows a high genetic variability (Ortíz-Dorda et al 2005), phytoextraction capacities may greatly vary from one population to another. Moreover, biotic parameters may also modify the phytoremedial potential of this species.…”
Section: Introductionmentioning
confidence: 99%